Presentation of an executable model for evaluation of software architecture using blackboard technique and formal models - Majidi, Fatemeh; Harounabadi, Ali (Journal of Advanced Computer Science & Technology, 2015)
Considering the promotion and complexities of software systems and need to services for repair and updating, success of this system is extremely dependent to its architecture and design. Architectural techniques due to being used by the architectures frequently have specified effect on qualitative characteristics. If this effect is quantitative and measurable for each technique will enable the architect to have more care and convenience for evaluation of design and architectural designs. In this study, at first to show the structure and behavior of software architecture using blackboard technique, component diagram and unified modeling language activity diagram together with required data in relation to nonfunctional needs as stereotypes and labels were used. Later, upon converting the actual model to the formal model, requirements for system performance evaluation on the formal model is provided. Upon analyzing the results, it is observed that the offered method can evaluate the performance of software architecture based on blackboard technique at the design age.